La représentation du genre au XIXe siècle. Masculinités dans le couple royal et la biographie de François d’Assise de Bourbon - Félix Colás Loricera (Cahiers de Civilisation Espagnole Contemporaine)
The royal couple formed by Isabel II and Francis of Assisi is particularly interesting because of the external and internal dynamics that marked a peculiar development that, in several aspects, marked the future of the Spanish monarchy and society. The internal dynamics are defined by the "inversion" of roles represented by the fact that Isabel was the monarch and Francis the consort, as well as by the dissident personalities of both. Isabel has been extensively studied in this respect, while Francis is a more obscure but equally relevant case study. With respect to external issues, the biography of Francis in his marriage is marked by the period of transition in 19th century notions of gender from traditional-aristocratic to Victorian-bourgeois society, a transition in which the couple was judged by various strata of society and from different points of view and canons of behaviour.